La suspensión provisional de los actos administrativos en la ley 1437 de 2011 (2016)
The provisional suspension has been listed as the power of the court to provisionally suspend the administrative acts when this is necessary to avoid serious irreparable injury significantly, which resulted figure since 1886 and the date is within the existing constitutional order. Administrative law regarding the temporary suspension of administrative acts had been always providing that certain conditions set out in Article 152 of the Administrative Code -CCA- were met and this was granted or refused by the same car admitted the demand. Later, with the enactment of Law 1437 of 2011, this figure has been incorporated into the precautionary measures and the procedure for granting or denying it should be done through a separate notebook, a circumstance that leads to investigate what the reasons were introduction of the suspension as a precautionary measure, and if this change would entail a greater desgate or not the judiciary compromising the speed that is precisely what the new law seeks orality. With regard to the above, the aim of this research is to build a procedural guide for those interested in the changes that created the new law of orality in administrative litigation (1437, 2011), for work reasons, as well as academic, from a personal and professional perspective to be public servants of a part of the judicial branch which came to orality with the effective date of the aforementioned law, trying to point out the advantages and disadvantages that could lead to the inclusion of the provisional suspension as a precautionary measure . Research carried out under the parameters concerning What are the main causes of the inclusion of the provisional suspension as a precautionary measure in the Law 1437 of 2011, new Administrative Code?